KHASHAISH KHATH AL TSULUTS WA MUMAYYIZATUHU WA ASRARUHU - Nurul Huda (Arabic Education Program IAIN Pekalongan, 2016)
Arabic calligraphy has been recognized by Indonesian society, especially in learning Arabic texts, such as Qurâ€™an and Hadith. Nowadays, it is not even used in a manuscript only, but also used as home and mosque decoration. There are many kinds of calligraphy letterform; one of them is called â€œS\â€ (khat S\). Sis the most used letterform both in calligraphy books and decoration. It may caused by the flexibility of its letterform and its elasticity of the structure that makes it looks charismatic. In this research, there is a new model of calligraphy which does not only depend on the history, but also relates to the secret or the meaning contained in the forming of Ṡn addition, there is also a description of a more comprehensive calligraphy style which makes the idiosyncrasies of Sare revealed in the forming of a calligraphy style.